1994
DOI: 10.1111/j.1748-5827.1994.tb03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Dystocia in the cat: A retrospective study of 155 cases

Abstract: In a retrospective study of 155 cases of feline dystocia, 67.1 per cent were of maternal origin, mainly caused by uterine inertia, while 29.7 per cent were of fetal origin, mainly resulting from malpresentations/malorientations and deformities. Its breed incidence was somewhat higher in Persian cats than in other breeds and considerably lower in Norwegian forest cats. Litter size was not related to the risk of developing dystocia. Ninety-seven cats (62.5 per cent) were treated with calcium and, or, oxytocin. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 3 publications
5
33
1
Order By: Relevance
“…After litters per year, litter size has the most dramatic impact on extrapolations of domestic cat reproductive potential. Mean litter sizes reported in the literature for free-ranging cats range from 2.1 to 5 kittens/litter, [5][6][7][8][9][10][11][12][13] and our study 5 found mean litter size to be 4.1 ± 1.3 (mean ± SD) on the basis of fetus number or 3.5 ± 1.2 on the basis of live births. These numbers, of course, do not take into account kitten mortality.…”
Section: What Do We Know About Feral Cat Reproductive Potential?supporting
confidence: 48%
“…After litters per year, litter size has the most dramatic impact on extrapolations of domestic cat reproductive potential. Mean litter sizes reported in the literature for free-ranging cats range from 2.1 to 5 kittens/litter, [5][6][7][8][9][10][11][12][13] and our study 5 found mean litter size to be 4.1 ± 1.3 (mean ± SD) on the basis of fetus number or 3.5 ± 1.2 on the basis of live births. These numbers, of course, do not take into account kitten mortality.…”
Section: What Do We Know About Feral Cat Reproductive Potential?supporting
confidence: 48%
“…These numbers are similar to those in previous studies. 15,31 Maternal causes, mainly uterine inertia, are the most common causes of dystocia in cats, 32 and in brachycephalic breeds foetal malpresentation is also common. 31 The effect of litter size was in litters with only one kitten probably due to insufficient stimulation to initiate labour, while in cases with larger litters overstretching of the myometrium causing inertia is a more likely cause.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that powerful uterine and abdominal contractions, excessive oxytocin stimulation, severe tenesmus, and uterine atony are predisposing factors of uterine prolapse (3,6). In contrast with Bigliardi et al (3) and Jutkowitz (6), the uterine prolapse in this case was thought to be due to prolonged parturition (8), dystocia (9), and repeated pregnancy (4). In accordance with the researchers, it was thought that contamination of the prolapsed tissue caused leukocytosis (10) and severe anaemia was a result of poor nutrition during gestation (11).…”
Section: Resultsmentioning
confidence: 78%